The live-work-play district: from vision to implementation - Jurey, Nathan W. D. (Kansas State University, 2012)
The concept of Live-Work-Play has grown in popularity in the field of planning, as various strands of the planning literature increasingly have highlighted the potential benefits of providing places to live, work, and play in close proximity. This study explores the theoretical foundations of the Live-Work-Play concept and discusses its effectiveness as a strategy for creating vibrant urban areas by reforming the spatial arrangement of the built environments. More specifically, the present study empirically examines how the segregation or the mixture of places to live, work, and play may create differences in terms of growth, inequality, education, the built environment, and transportation by analyzing the Boston metropolitan region as an example. The empirical analysis with the use of census tract level socio-economic data shows that the Live-Work-Play mixes can encourage more desirable travel patterns, while the mixes may not significantly promote growth in small areas. However, the analysis also revealed racial and income inequalities exist in the provision of the mixes in the Boston region. These findings suggest planners carefully should consider the equity issues when adopting the Live-Work-Play concept and providing its potential benefits.
Keywords: Mixed use; Planning; Boston; Spatial mismatch; Transportation efficiency; Economic development; Area Planning and Development (0341); Land Use Planning (0536); Urban Planning (0999)